2021
DOI: 10.1155/2021/6830459
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Toxicokinetics of Artemisinin-Hydroxychloroquine Sulfate Tablets in Rats and Dogs

Abstract: Artemisinin-hydroxychloroquine sulfate tablets (AH) are relatively inexpensive and a novel combination therapy for the treatment of all forms of malaria, especially aminoquinine drug-resistant strains of P. falciparum. Our aim was to assess the pharmacokinetics (PK) and toxicokinetics (TK) of AH following oral administration in Sprague Dawley rats and Beagle dogs by using the liquid chromatography tandem mass spectrometry methods (LC-MS/MS). The PK studies were carried out in eighteen rats at three doses and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The instrument settings and performance metrics are described in detail in Figure A5. The LLOQ for HCQ was 10 times improved over two recently reported LC–MS/MS methods 10,11 …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The instrument settings and performance metrics are described in detail in Figure A5. The LLOQ for HCQ was 10 times improved over two recently reported LC–MS/MS methods 10,11 …”
Section: Methodsmentioning
confidence: 89%
“…The observed C max values for HCQ were in good agreement with reported values by other authors. For example, in rats orally dosed with low, mid, and high doses of HCQ and artemisinin combination tablets, corresponding to an intake of 82, 165, and 331 mg HCQ/kg, the plasma C max mean values were 402, 623, and 868 ng HCQ/mL, respectively 11 . A 2023 preprint in Medrxiv (https://www.medrxiv.org/content/10.1101/2023.06.22.23291702v1) documented an oral dosing of 13.3 mg HCQ/kg to rats resulting in C max of 90 ng HCQ/mL plasma and 183 ng HCQ/mL whole blood.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown pharmacokinetic evidence of reduced clearance in female rats ( Li et al, 2021 ; Arora et al, 2021 ; Zhou et al, 2002 ; Czerniak, 2001 ). Gender differences in clearance mechanisms are complex and may depend on the formulation ( Soldin et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the absorption of artemisinin in the body has apparent gender and individual differences. After continuous oral administration of artemisinin in rats for five days, the AUC0∼t of females and males decreased by 63.5% and 56.4%, and the maximum plasma concentration (Cmax) decreased by 66.8% and 55.8% ( Li et al, 2021 ).…”
Section: Pharmacological Characteristics Of Artemisinin and Its Deriv...mentioning
confidence: 99%